Gender differences in caregiving among family - caregivers of people with mental illnesses - Sharma, Nidhi (World J Psychiatry, 2016)
All over the world women are the predominant providers of informal care for family members with chronic medical conditions or disabilities, including the elderly and adults with mental illnesses. It has been suggested that there are several societal and cultural demands on women to adopt the role of a family-caregiver. Stress-coping theories propose that women are more likely to be exposed to caregiving stressors, and are likely to perceive, report and cope with these stressors differently from men. Many studies, which have examined gender differences among family-caregivers of people with mental illnesses, have concluded that women spend more time in providing care and carry out personal-care tasks more often than men. These studies have also found that women experience greater mental and physical strain, greater caregiver-burden, and higher levels of psychological distress while providing care. However, almost an equal number of studies have not found any differences between men and women on these aspects. This has led to the view that though there may be certain differences between male and female caregivers, most of these are small in magnitude and of doubtful clinical significance. Accordingly, caregiver-gender is thought to explain only a minor proportion of the variance in negative caregiving outcomes. A similar inconsistency characterizes the explanations provided for gender differences in caregiving such as role expectations, differences in stress, coping and social support, and response biases in reporting distress. Apart from the equivocal and inconsistent evidence, there are other problems in the literature on gender differences in caregiving. Most of the evidence has been derived from studies on caregivers of elderly people who either suffer from dementia or other physical conditions. Similar research on other mental illnesses such as schizophrenia or mood disorders is relatively scarce. With changing demographics and social norms men are increasingly assuming roles as caregivers. However, the experience of men while providing care has not been explored adequately. The impact of gender on caregiving outcomes may be mediated by several other variables including patient-related factors, socio-demographic variables, and effects of kinship status, culture and ethnicity, but these have seldom been considered in the research on gender differences. Finally, it is apparent that methodological variations in samples, designs and assessments between studies contribute a great deal to the observed gender differences. This review highlights all these issues and concludes that there is much need for further research in this area if the true nature of gender differences in family-caregiving of mental illnesses is to be discerned.